Pemanfaatan Limbah Obat Kedaluwarsa sebagai Adsorben dalam Pengolahan Air Limbah Rumah Sakit: Bahasa Indonesia - Nurul Arsy; Risanyel Elsan Tuturop; Aisya Usili (LRI Universitas Muhammadiyah Sorong, 2026)
Expired pharmaceutical waste is increasingly recognized as a significant environmental pollutant due to its persistent active compounds that can contaminate water systems. Hospitals generate substantial amounts of pharmaceutical waste, including unused liquid and solid drugs. This study aims to utilize expired drugs as raw material for adsorbent production through carbonization and chemical activation processes, thereby offering a sustainable solution for hospital wastewater treatment. The methodology involved collecting expired drugs, subjecting them to high-temperature carbonization, and applying chemical activation to enhance surface area and adsorption capacity. Adsorption tests were conducted on hospital wastewater samples, focusing on COD, BOD, and heavy metal parameters. Results demonstrated that drug-derived adsorbents reduced COD and BOD levels by up to 60% and showed significant efficiency in heavy metal removal. Compared to commercial adsorbents, the performance of expired drug-based adsorbents was competitive, while also being cost-effective and environmentally friendly. This research highlights the dual benefits of reducing pharmaceutical waste and providing an alternative adsorbent material for wastewater treatment. The findings support the concept of circular economy in pharmaceutical waste management, emphasizing resource recovery and environmental sustainability.